Characteristics of Strong Ground Motions in the 30 October 2020, MW6.9 Aegean Sea Earthquake - Malcioglu, Fatma Sevil; O’Kane, Aisling; Donmez, Kokcan; Aktas, Yasemin D. (Frontiers in Built Environment, 2022)
The eastern parts of the Aegean Sea were struck by a destructive MW 6.9 earthquake on October 30th, 2020 at 11:51:27 UTC. The earthquake ruptured an East-West trending normal fault in the Aegean Sea between the northern coast of Samos Island and the southern coast of İzmir and also triggered a medium level tsunami and thousands of aftershocks across the region. 119 fatalities, 1051 injuries, and many collapsed buildings were reported due to the earthquake in the affected region. The most catastrophic consequences of the earthquake were registered in the Bayraklı and Bornova districts, which are built on a deep alluvial Basin approximately 60-70 km away from the epicentre of the mainshock. This paper explains the damage with an extensive dataset of ground motion records of the mainshock and aftershocks, which are provided by both Greek and Turkish networks. A set of ground motion parameters such as peak ordinates, spectral quantities, intensity measures and duration parameters are calculated and analysed. The closest softer soil station in Samos Island produces the highest peak ground acceleration and velocity. The ground motion models employed commonly for the region overestimate the observed data beyond 60-70 km of Joyner-Boore distance except for the recently published local ground motion model, which utilises local earthquakes in the derivation of the model. Contrary to expectations, stiff soil recordings exhibit considerable spectral accelerations in the long period region, similar to those in soft soils. The calculated ground motion parameters are correlated with the results of the hybrid reconnaissance mission, organized by the Earthquake Engineering Field Investigation Team (EEFIT). Although the peak values and regarded intensity measures clearly highlight the variability in soil conditions in the most damaged area (Bayraklı and Bornova), velocity-based ground motion parameters seem to be the more responsive damage indicators. The spectral shapes of the normalised response spectra in the İzmir Basin are not compatible with the 2018 Turkish seismic code spectrum whereas their response spectra are below the 475-year return period design spectra provided in outdated and current Turkish seismic codes.